Ethnomethodological Study of The Disclosure of Good Government In Cingkreman Practices - Eka Putri Suryantari; Diah Citra Resmi Cahyadi; I Wayan Suarjana (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This study aims to reveal the existence of good governance practiced in cingkreman, namely the practice of family financial planning based on social values, cultural life and religious activities of Hindus carried out by community groups in a community based on group beliefs and agreements. Method: This research is a qualitative study using an interpretive paradigm and an ethnomethodological approach. Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis was then carried out using Garfinkel Analysis. Results: The results of this study successfully revealed the existence of good governance in Sekaa Cingkreman. The findings of this study provide an overview that the good governance implemented in Sekaa Cingkreman is a crucial foundation for realizing the sustainability of an informal organization formed from shared interests and social agreements, namely conducting financial planning to meet the needs of implementing religious and cultural activities. Conclusion: This research provides theoretical implications and enriches the study of good governance and plays a role in the sustainability of the cingkreman practice as a culture-based financial planning practice. Therefore, it can be used in future scientific studies in culturally-based financial planning research and research on good governance. The novelty of this research is that it reveals the application of good governance in a culture-based financial planning practice carried out by parties who are members of the Sekaa Cingkreman